Exploring Stress of Part-Time FPTV Students with Self-Efficacy and Students Academic Achievement - Ab Rahim, Filzah Aqilah; Hashima Hamid (Research and Innovation in Technical and Vocational Education and Training, 2025)
Mental health problems, the rate of student failure in completing their studies are seen to be closely related to stress and student self-efficacy. The stress encountered can affect the well-being of students and thus affect their academic achievement. This study was conducted to find out the types of stress faced by part-time students, how part-time students manage stress, and see how self-efficacy in academics and the stress they face affect their academic achievement. Several research questions were posed to answer this question. The study was conducted on final year MBV part-time students from the Faculty of Technical and Vocational Education, Universiti Tun Hussein Onn Malaysia. The study was designed as a case study and using qualitative approach. A total of six participants were interviewed to obtain study data. The data analyzed using thematic analysis to obtain the theme. The results of the study found that student self-efficacy, stress and student academic achievement are closely related and MBV part-time students have four sources of self-efficacy based on Bandura’s Self-Efficacy Theory as their way or coping mechanism in facing challenges throughout their studies. In conclusion, various types of stress faced by part-time students are because they are faced with various commitments. Therefore, strategic coping mechanisms are needed to overcome these challenges to prevent stress from becoming more and more unbearable and subsequently affecting their emotional and physical health.